NEGARA ISLAM DAN ISLAM NUSANTARA DALAM WACANA VISI MISI CAPRES 2019: KAJIAN WACANA KRITIS DAN POSTMODREN - Kholid Kholid (Universitas Nahdlatul Wathan Mataram, 2019)
The purpose of this study is to describe a discourse in the vision and mission of the 2019 presidential candidate on the Islam Nusantara and the Islamic State. The Islam Nusantara and the Islamic State Discourse became a polemic to both of the presidential candidate’s supporters in the current 2019 democratic contestation situation. This study uses postmodern theory as a foothold in analyzing phenomena or polemic on linguistic perspectives, by looking at the arguments of those who agree and those who disagree with the Islam Nusantara and the Islamic State discourse. This study uses qualitative descriptive methods to understand and describe both discourses. Observation, interviews and documentation are conducted in collecting data. Analyzing data is conducted by classifying several pro and contra arguments to Islam Nusatara and the Islamic State discourse, and then the arguments are described by providing linguistic perspective interpretations.